BTS Engineering Sdn Bhd / Wan Nur Asyiqin Wan Roslee - Wan Roslee, Wan Nur Asyiqin (Faculty of Civil Engineering, 2015)
Industrial Training is a compulsory requirement for students in certain programs at all levels of higher education in Institutions of Higher Learning (IHL). To increase the level of graduates able to work, industrial training program was introduced to strengthen the competencies required. Industrial Training courses give students learning opportunities in the world of work to receive practical experience in order to improve the reliability of the market. Industrial Training refers to expose students to the real-life experiences of the engineering works and to get them involved in Civil Engineering projects before graduation. It is one of the requirements for the award of Diploma in Civil Engineering is that the student must complete at least seven (7) weeks of Industrial Training. Industry training is usually collected during the semester break at the end of the third year student (semester 4 and above). The technical and non-technical outcomes of the course may be assessed and evaluated through this industrial training. This industrial training have several objectives that have to be done, for example appreciation of client's requirement, attending site visits, interpretation of construction drawings, interpretation of contract specification and involvement in project management, discussion with visiting lecturer and preparation of report. In addition, other activities relevant to the training, as directed by the supervisor can also be included. From this project, I would be able to practice good working ethics and quality delivery of project undertaken. Thus, I also would be able to exhibit pleasant interpersonal skills as an individual in working independently, collaborative and in multi-disciplinary team. Furthermore, I can practice good organizational skills in enhancing individual and group effectiveness and productivity. Besides, I would be able to exhibit good communication with fellow workers and supervisors in issues related to projects undertaken.